Distribution of exogenous complement factor H in mice invivo - Koskinen,AR; Cheng,Z-Z; Pickering,MC; Kairemo,K; Meri,T; Cook,HT; Meri,S; Jokiranta,TS (Scandinavian Journal of Immunology, 2018)
Factor H is an important regulator of complement activation in plasma and on cell surfaces in both humans and mice. If FH function is compromised, inappropriate complement activation on selfsurfaces can have disastrous effects as seen in the kidney diseases atypical haemolytic uremic syndrome (aHUS) and C3 glomerulopathy. As FH constructs have been proposed to be used in treatment for these diseases, we studied the distribution of exogenous FH fragments in mice. Fulllength mFH, mFH15 and mFH1820 fragments were radiolabelled, and their distribution was examined in WT, FH−/− and FH−/−C3−/− mice in vivo. Whole body scintigraphy revealed accumulation of radioactivity in the abdominal part of the mice, but also to the thyroid gland and urinary bladder. At organ level in WT mice, some fulllength FH accumulated in internal organs, but most of it remained in the circulation. Both of the mFH fragments accumulated in the kidneys and were excreted in urine. For mFH15, urinary secretion is the likely cause for the accumulation. Concentration of mFH1820 to kidneys was slower, and at tissue level, mFH1820 was localized at the proximal tubuli in WT and FH−/−C3−/− mice. No C3independent binding to glomeruli was detected. In conclusion, these results show that glomerular glycosaminoglycans and sialic acids alone do not collect FH in kidneys. Deposition of C3 fragments is also needed, which implies that in aHUS, the problem is in simultaneous recognition of C3 fragments and glycosaminoglycans or sialic acids by FH, not just the inability of FH to recognize glomerular endothelium as such.